Group processes : dynamics within and between groups - Brown, Rupert (Malden, MA : Blackwell Publishers, 2000)
This second edition of Group Processes aims to deepen the understanding of the reader regarding the relationships within and between groups by means of three key ideas. First, groups are a source of social identity; our sense of who we are and what we are worth derives from our group memberships. Second, there is a constant tension in group life between its task and socio-emotional aspects; "getting on with the job" whilst also "getting on with people." Third, group dynamics are frequently governed by comparison processes, both within the group and between the ingroup and various outgroups. In this revised edition, Brown introduces readers to the major developments in the field of group processes. All the chapters were thoroughly updated and several new sections have been added.
The reality of groupsElementary processes in groupsStructural aspects of groupsSocial influence in groupsIndividuals versus groupsIntergroup conflict and cooperationThinking about groupsSocial identity and intergroup relations
Keywords: socijalna psihologija; grupni procesi; grupna dinamika; integrupna dinamika; vođenje; intergrupni konflikt; intergrupna kooperacija; socijalni identitet; grupna produktivnost; donošenje odluka u grupi; vođenje; kohezija; grupne norme